Prevalence and severity of vasomotor symptoms and joint pain in women at midlife in Bangladesh: a population-based survey. Issue 7 (July 2016) - Islam, Rakibul M.; Bell, Robin J.; Billah, Baki; Hossain, Mohammad B.; Davis, Susan R.
Abstract: Objective: The aim of the study was to document the prevalence of menopausal symptoms and the extent to which women are bothered by vasomotor symptoms (VMS) and joint pain in Bangladesh. Methods: A total of 1, 590 women, aged 30 to 59 years, participated in a cross-sectional, questionnaire-based study between September 2013 and March 2014. The main outcome measures were moderate to severely bothersome VMS and joint pain, measured by the Menopause-Specific Quality of Life questionnaire. Results: Of participants, 59.4% were premenopausal, 8.4% perimenopausal, and 32.3% postmenopausal. Approximately all women reached menopause by the age of 50 years. The prevalence of moderate to severely bothersome VMS was 4.1% in premenopausal, 33.3% in perimenopausal, and 28.2% in postmenopausal women. Factors associated with moderate to severely bothersome VMS were being perimenopausal (odds ratio [OR] 46.34, 95% CI 13.29-161.56; P  < 0.001) or postmenopausal (OR 19.15, 95% CI 5.63-65.11; P  < 0.001) and obesity (OR 2.20, 95% CI 1.03-4.71; P  = 0.042). The prevalence of moderate to severely bothersome joint pain was 40.3% in postmenopausal, 36.2% in perimenopausal, and 15.3% in premenopausal women. Moderate to severely bothersome joint pain was more likely both in perimenopausal (OR 2.64, 95% CI 1.63-4.29; P  < 0.001) and postmenopausal women (OR 2.96, 95% CI 2.06-4.24; P  < 0.001). Moderate to severely bothersome joint pain was also more likely in women with no education compared with women having education beyond secondary school (OR 2.38, 95% CI 1.02-2.32; P  < 0.001). No women reported prescription therapy for menopausal symptoms. Conclusions: This study demonstrates that a high proportion of Bangladeshi women experience moderate to severely bothersome VMS and joint pain. Despite the considerable symptom prevalence, no women reported treatment, suggesting that menopause remains neglected in Bangladesh.